Livestock Production in Nigeria: Our Commissions and Omissions - Ademosun, A.Akin (Obafemi Awolowo University Press, 2013)
The livestock mission appointed in Nigeria by the Colonial Office in 1949 was probably the first to draw attention to the problems of livestock production in the country and the need to develop the industry. Since the report of the Mission in 1950, many attempts have been made to obtain data on the numbers of the different species of farm animals in Nigeria. The amount of success that has attended this exercise has been, at best, similar to that of the counting of human beings and has generally under-scored the famous statement of Benjamin Disraeli: "There are three kinds of lies: lies, damned lies and statistics." The question of census figures is even confounded in the case of animals because they never contest the statistics nor do they ask for any post-enumeration checks, for as George Eliot stated: "Animals are such agreeable friends-they ask no questions, they pass no criticisms."